Sampling Techniques for Estimating Tree Growth and Volume by Selection of Sample Trees for Measurement within Individual Sample Plots. - Rawat, A. S. (Indian Forester, 1949)
On the evidence of the results obtained from the data of 5 clearfelled sample plots of different ages, species and localities, the following conclusions may be drawn: 1. The present method of selection of sample trees for measurement in a sample plot, is a biased method which always gives higher figures than the actual values as well as those derived by random sampling both with and without stratification. 2. The current method (based on Schwappach’s height and form factor curve method) may be replaced by stratified random sampling scheme which has given more satisfactory results than the former. 3. To estimate tree growth and volume of a sample plot by stratified random sampling design, with sufficient precision for all practical purposes, a sample should consist of at least 15 trees.